STRATEGI MANAJEMEN SARANA DAN PRASARANA DAPAT MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Anik khusniah; Taufiq Harris; furqon wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The management of infrastructure and facilities is a crucial aspect of successful educational delivery, particularly at the Elementary School level, which serves as the foundational stage for student development. This study aims to analyze how effective management of facilities and infrastructure can directly contribute to improving the quality of education in Elementary Schools. The research method employed is descriptive qualitative through literature review and policy document analysis. The findings indicate that ideal infrastructure management comprising data-driven needs planning, transparent procurement, orderly inventory, routine maintenance, and proper asset disposal is capable of creating a conducive learning environment, increasing student motivation, and supporting teacher pedagogical effectiveness. The quality of education in Elementary Schools is proven to enhance significantly when the fulfillment of physical facilities is integrated with the utilization of educational technology and curriculum demands. The implications of this research emphasize the urgent need for visionary principal leadership and government support in proportional budget allocation for school facility management.